Determinants That Affect Patient Safety At Work: A Literature Review - Sumiati; Ratna Wardani; Yuly Peristiowati (Journal of Global Research in Public Health, 2023)
Nursing practice is sometimes found that patient safety is carried out by nurses at work so that this raises concerns for the public to seek treatment.To determine the determinants that affect patient safety at work.This systematic review begins with a literature review from various sources. Articles were collected using search engines such as PubMed, google schoolar, science direct, ProQuest and Elsevier. The articles used in the study were published from 2018-2023. Articles were searched using keywords that have been determined by the researcher then articles were extracted based on inclusion and exclusion criteria using the PRISMA protocol. Thus, 15 articles were found that matched the critical appraisal criteria for analysis.Based on the articles collected, it was found that patient safety is a topic that has been the subject of much discussion in recent decades. Patient safety is defined as failure to accomplish what was planned or achieving something using the wrong means. In brief, there are two elements to patient safety: a plan and an aim. This means that there are two possible causes of error: the medical provider made the wrong plan and the patient was injured, and the provider made the right plan but there was an error in execution that caused the patient to be injured. These errors can occur due to several things, such as work environment disorders, fatigue, lack of team coordination, and communication failures.Communication, environmental conditions, workload, distraction at work, and staff education are factors that significantly affect patient safety at work. It is expected that nurses in providing health services must improve quality which will be able to provide comfort and quality service to patients in terms of improving patient safety.